REFLECTION OF ISLAMIC METAPHYSICS IN THE WORKS OF IBN SINA - Isakdjanov Ramziddin (American Journals, 2023)
Islamic philosophy, in particular, Ibn Sina's views on metaphysics have been carried out by scientists. In these studies, the contributions of some scientists and philosophers who lived and worked in Central Asia to the development of science, the influence of Eastern philosophy on European scientists, the spread of Islam and Sufism, and the science of the word are described. Although the results of these studies originate from the features of the 9th-10th centuries, they play an important role in the analysis of epistemological and epistemological issues of today's Islamic philosophy.
Keywords: The question of the eternity of the universe, theology, metaphysics, Al-Mabda val ma'ad, Ash-Shifa, An-Najat, Wajib al-wujud.